2006
DOI: 10.1007/s00253-005-0299-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genetic diversity in Ganoderma population with a novel molecular marker SRAP

Abstract: Genetic marker technology designed to detect naturally occurring polymorphisms at the DNA level had become an invaluable and revolutionizing tool for both applied and basic studies of fungi. To eliminate the confusion on the taxonomy of Ganoderma strains, in this study, a collection of 31 accessions representative of morphotypes and some unclassified types was used for analyzing molecular diversity using a novel molecular marker sequence-related amplified polymorphism (SRAP). This collection included commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 17 publications
4
49
0
2
Order By: Relevance
“…The 5.8S gene that located between the ITS I and II regions was very well conserved (158 bp in length). The 5.8S rDNA sequences of the basidiomycetes fungi were identical, which was a result agreeing with our findings (Sun et al, 2006). Nucleotide sequence in the FIPs gene varied in length from 333 bp to 336 bp, with 100% consensus positions and 77.1% identity positions (Fig.…”
Section: Sequence Analysissupporting
confidence: 80%
See 2 more Smart Citations
“…The 5.8S gene that located between the ITS I and II regions was very well conserved (158 bp in length). The 5.8S rDNA sequences of the basidiomycetes fungi were identical, which was a result agreeing with our findings (Sun et al, 2006). Nucleotide sequence in the FIPs gene varied in length from 333 bp to 336 bp, with 100% consensus positions and 77.1% identity positions (Fig.…”
Section: Sequence Analysissupporting
confidence: 80%
“…Now, a variety of sequence-based DNA fingerprinting techniques have been used to the identification of cultivation of Ganoderma, such as internal transcribed spacer (ITS) 25S ribosomal DNA sequencing PCR amplification (Moncalvo et al, 1995;Gottlieb et al, 2000;Hong and Jung, 2004;Sun et al, 2006), PCR-RFLP (Zhou et al, 2008;Park et al, 2012), sequence characterized amplified region (Xu et al, 2008) and sequence-related amplified polymorphism molecular marker system (Sun et al, 2006). The use of these techniques is dependent on the ribosomal RNA sequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the various molecular marker techniques available, sequence-related amplified polymorphism (SRAP) is a novel third-generation technique. The SRAP protocol is a polymerase chain reaction (PCR) based marker system designed to amplify open reading frames (ORFs) [12,13]. The protocol is simple, efficient, and has a high production rate.…”
Section: Introductionmentioning
confidence: 99%
“…For example, G. lucidum HG is typically grown in Northern and North-Eastern China in cold environments, while G. tropicum is grown in tropical forests. A sequence-related amplified polymorphism analysis by Sun et al (2006) revealed significant genetic variation between G. lucidum and G. sinense. Zhao et al (2003) showed 80-100% polymorphism in genetic materials in different Ganoderma species, and Mei et al (2014b) showed high levels of genetic distance between G. gibbosum, G. tropicum, G. sinense, and G. lucidum.…”
Section: Discussionmentioning
confidence: 99%